Traditional Chinese medicines and Alzheimer's disease - Tzong-Yuan Wu; Chip-Ping Chen; Tzyy-Rong Jinn (Elsevier, 2011)
Traditional Chinese medicines have been widely investigated for the treatment of Alzheimer's disease (AD) because none of the current therapies-either the cholinesterase inhibitors or antagonist of N-methyl-d-aspartate receptors-has profound effects on halting the progression of AD. In recent years, scientists have isolated many active compounds from herbs, which can alleviate dementia and neurodegenerative syndrome with fewer side effects than conventional drugs and, thus, are regarded as promising drug candidates for AD therapy. In this review, we summarize the latest research progress on six herbs for AD therapy-Huperzia serrata, Amaryllidaceae family, Ginkgo biloba, Uncaria rhynchophylla, Polygala tenuifolia, and Salvia officinalis-and focus on the analysis of their active components and possible mechanisms of pharmacological actions on AD.